Residual stress measurement of laser cladding & weld specimens - Kang, Pei Ying (Nanyang Technological University, 2020)
In recent years, laser cladding technology has been attracting extensive research interest owing to its promising advantages such as low porosity, low dilution, swift process speed of up to 3 m/min, and excellent surface uniformity with very minimal roughness. Examples of laser cladding applications can be vastly seen particularly in the field of reconditioning works of expensive components and developing functional surfaces to extend the life span and functionality of the components. While laser cladding is a powerful technique in the field of surface processing, this technique is not without any setbacks. A significant problem relating to the laser cladding work is the generation of residual stresses in the clad material. The major causes for this to occur are attributed to the thermo-mechanical effects that are linked to the high thermal gradients inherent in the process and the differential thermal contraction. These residual stresses may result in more damage to the target components such as drops in fatigue strength and cracks. Therefore, it is vital for the laser cladding adopters to be able to understand, predict, and measure the formation of residual stresses in order to minimize the chances of poor coating quality. The project report outline is as follows: Review the fundamentals of laser cladding, residual stress, and also some existing techniques used for residual stress measurement. Following that, studies were conducted using a portable device known as the Pulstec X-ray Residual Stress Analyzer that applies the non-destructive X-ray diffraction method to measure the residual stresses of post-grind cladded rail specimens. The specimens were prepared via grinding (manual grinding and Computerized Numerical Control (CNC) grinding) post lasser cladding surface treatment. The experimental results shown that residual stresses in CNC grind-prepared specimen is more consistent than that of grind specimens which is as expected due to the differences in surface uniformity between manual and CNC grind operations. Moreover, data collated from both experiments also indicate the performance of the portable Pulstec X-ray Residual Stress Analyzer is sufficient for industrial applications particularly when on-site measurements are needed. As compared to other conventional mechanical release methods, X-ray diffraction measurement is much simpler, hassle-free, non-contact, and adaptable to a broad range of machining geometries and sizes. Futhermore, the fast measurement speed of this analyser enables a large volume of data to be collected in a short time frame to improve the accuracy and reliability of data analysis. One drawback observed from the results is that the accuracy of this analyser is affected by surface roughness of the specimens. This is because a high degree of surface roughness may have exceeded the penetration depth of the X-ray energy or wavelength, causing the inability of the analyser to sampled below the roughened surface. In addition, compressive residual stress at the clad surface is below the yield strength value of the cladded rail steel. Thus, when residual stress is greater than the yield stress of the cladded rail steel, plastic deformation will occur. Therefore, detailed research is required on the type of specimen and materials or future residual stress measurement trials.